Reactive Nitrogen in Crop, Fishery and Livestock Sectors of Bangladesh - Rahman, Md Mizanur; Biswas, Jatish Chandra (The Agriculturists, 2020)
Agriculture in Bangladesh is characterized by crop, fishery and livestock sectors. Urea-N is used in all three sectors. Crop sector plays a dominant role in urea consumption to supply of food for ever burgeoning population. Application of inorganic N fertilizer definitely increased agricultural productivity. This however playing a significant role in altering global nutrient budget, water quality, greenhouse gas emission, and ultimately affecting the global climate. Though cropping intensity and use of N fertilizer have increased, yield plateauing is a concern for food security. Recovery efficiency of N rarely exceeds 30% in both crop and fish culture, while remaining reactive N is a global concern. Different industries have emerged in the last decade producing huge amounts of effluents discharging to the environment without treatment which appeared as a potential threat in damaging and disintegrating the environment. Resultant negative effect from application of large amount of organic and inorganic fertilizers and feeds in fishponds is a matter of boundless anxiety as it might act as a source of reactive N. Livestock sector comprising poultry and dairy produce huge amount of manure annually which is equivalent to 0.30 million tons of N and because of poor manure management reactive N is spreading in the environment. Reluctant attitudes on these crucial issues might bring a disaster through stopping natural ecosystem functions of the environment from where ‘U’ turn will rather be impossible. Adoption of resource conservation strategies, judicial and optimum use of N fertilizers in all agricultural sectors, improved management of livestock manure and industrial effluents are strongly recommended for environmental sustainability. The Agriculturists 2020; 18(1) 144-163